Stabilitas Sediaan Lotion Ekstrak Herba Sawi Langit (Vernonia cinerea (L.) Less) Dengan Menggunakan Stearil Alkohol Sebagai Emulgator - Auliah Rahmi Latif; Anisa Dwirizky Abdullah (KOLONI, 2023)
Stability Test of Preparation Lotion extract Sawi Langit (Vernonia cinerea (L) Less) herbal with stearyl Alcohol as an emulsifier. The purpose of this study was to determine the ability of stearyl alcohol as an emulsifier in the preparation of lotion extract Sawi langit herba as well as to determine the level of stability of the preparation. The lotion is formulated with a variety of emulsifier stearyl alcohol concentrations of 1% b/b, 3% b/b, and 5% b/b. Evaluation lotion was conducted for 2 weeks include: organoleptic preparations have colors, shapes, and smells of stable, power of dispersive at concentration 1% b/b and 3% b/b qualify the power of dispersive preparation lotion is 7cm-14cm, the pH value of 50C storage stable and 250C storage stable at concentration of 1% b/b and 3% b/b because it has suitable pH of the skin 4.5-6.5 and pH of good lotion is 4.5-8.0. Keywords: Stability Test, Lotion, Extracts Sawi Langit Herbal, stearyl alcohol emulsifier